Egzamin General Certificate of Secondary Education (GCSE) jako narzędzie budowania prestiżu języka polskiego w Wielkiej Brytanii – opinie nauczycieli szkół polonijnych, działania instytucjonalne - Lewińska, Aneta; Czerwińska, Anna (Neofilolog, 2026)
In the United Kingdom, the number of students taking Polish at GCSE has been increasing for twenty years, which has had a significant impact on the growing prestige of the Polish language in each of the constituent countries. This is largely thanks to teachers in Polish Saturday schools who motivate students to take on the challenge of studying an additional subject for their exams. The article presents the results of a 2025 survey conducted among Polish language teachers preparing students for the GCSE exam. Respondents cited many motivators encouraging students to take Polish at GCSE, of which the specific benefits that this exam offers in the British education system were considered the most important. Other reasons were also mentioned – shaping national identity, pride in knowing their heritage language, success of students in previous years, interesting activities at Polish Saturday schools in a close group of peers, and support from the community. The support of Polish and British institutions promoting the teaching of Polish at GCSE level is also discussed, and it is shown how the British media, writing about this exam, are building the prestige of the Polish language.